Will Smith’s Acceptance Speech At The 94th Academy Awards; Seeking Justification With Pathos And Ethos Appeal - Andita Putri Purnama (Syntax Corporation, 2022)
The 94th Academy Awards ceremony in 2022 will be the most memorable moment in history because the unexpected event of actor Will Smith slapping comedian Chris Rock in front of the audience and broadcast live on television. Not long after the incident, Will Smith was named best actor and had to deliver a short speech when receiving the award. It is interesting to analyze the points of Will Smith's speech after the slapping he did. This study analyzes Will Smith's speech when he received an award using rhetorical analysis by describing the elements of logos, ethos and pathos. The results of the analysis show that Will Smith's speech contains points that put forward elements of Pathos and Ethos to seek justification for his actions and to gain public sympathy.